2019
DOI: 10.3390/nu11040711
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Long-Chain Fatty Acids and Cognitive Performance in Older Australian Adults

Abstract: Convincing evidence exists for the positive effect of an improvement in diet quality on age-related cognitive decline, in part due to dietary fatty acid intake. A cross-sectional analysis of data from the Hunter Community Study (HCS) (n = 2750) was conducted comparing dietary data from a validated Food Frequency Questionnaire (FFQ) with validated cognitive performance measures, Audio Recorded Cognitive Screen (ARCS) and Mini Mental State Examination (MMSE). Adjusted linear regression analysis found statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Today, the Western diet has a ratio of about 17 to 1 n-6 to n-3 fatty acids, meaning most Americans have a lot more LA, AA, and DPA in their bodies, which are able to produce relatively large quantities of inflammatory and oxidative mediators (Simopoulos, 2006). Increased ratios of n-6 to n-3 dietary fatty acids have also been directly associated with increased cognitive decline and risk of AD (Loef and Walach, 2013;MacDonald-Wicks et al, 2019). DHA, on the other hand, an n-3 LC-PUFA usually found in fish and algae, is not largely found in the Western diet.…”
Section: Dietmentioning
confidence: 99%
“…Today, the Western diet has a ratio of about 17 to 1 n-6 to n-3 fatty acids, meaning most Americans have a lot more LA, AA, and DPA in their bodies, which are able to produce relatively large quantities of inflammatory and oxidative mediators (Simopoulos, 2006). Increased ratios of n-6 to n-3 dietary fatty acids have also been directly associated with increased cognitive decline and risk of AD (Loef and Walach, 2013;MacDonald-Wicks et al, 2019). DHA, on the other hand, an n-3 LC-PUFA usually found in fish and algae, is not largely found in the Western diet.…”
Section: Dietmentioning
confidence: 99%
“…In a study where FFAs intake was assessed with the use of nutritional questionnaire, the authors indicated a lower risk of AD with an increasing intake of n3 PUFAs such as DHA and EPA [ 12 ]. Dietary intake of n-6 fatty acids was connected with better cognitive functions, but such an observation was not elucidated for other FFAs [ 13 ]. Higher levels of omega-6 FFAs consumption including AA were reported to be associated with an increased risk of dementia [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to a healthy dietary pattern is emerging as a promising lifestyle behaviour that may protect against age-related cognitive decline [1]. More specifically, diets high in nutrients such as B-vitamins, monounsaturated fatty acids (MUFA), polyunsaturated fatty acids (PUFA), and antioxidants (e.g., beta-carotene, vitamin C) are reported to have neuroprotective properties involved in maintaining cognitive health in later adulthood [2][3][4]. In contrast, diets high in saturated fatty acids and simple carbohydrates are associated with poor age-related cognitive functioning [5].…”
Section: Introductionmentioning
confidence: 99%